Development of Teaching Materials in The Islamic Religious Education Curriculum at Madrasah Aliyah - Marhamah Marhamah; Maisarah Maisarah; Zikriati Zikriati; Rahmat Saputra; Hanifa Salsabila (Jurnal Ilmiah Teunuleh, 2026)
The development of Islamic Religious Education (PAI) learning materials in Madrasah Aliyah plays a strategic role in fostering competencies as well as a harmonious and contextual religious character in students. A challenge that frequently arises in current learning practices is the utilization of instructional materials that tend to be textual, lack contextuality, and are not fully adaptive to student characteristics or the demands of the latest curriculum. This study aims to examine the nature of materials, learning resources, development principles, types of content, as well as the techniques and designs for compiling PAI instructional materials at the Aliyah level that are relevant to students' competency needs. Utilizing a qualitative approach in the form of a literature review, this study analyzes various literatures relevant to the subject matter under internal investigation. The results of the study indicate that the design of PAI learning materials must be executed systematically, integratively, and contextually by balancing the cognitive, affective, and psychomotor dimensions. Furthermore, the implementation of PAI instructional materials needs to integrate essential values such as the "Love Curriculum", religious moderation, and ecotheology. Through this integration, PAI learning is not merely oriented toward conceptual mastery, but also focuses on character building, humanistic values, and students' socio-ecological awareness. Designing materials that align with learning outcomes and contemporary advancements is proven to enhance effectiveness and cultivate a PAI learning paradigm that is more reflective, dialogic, and student-centered in Madrasah Aliyah.